Optimisation of various physicochemical variables affecting molybdenum bioremediation using Antarctic bacterium, Arthrobacter sp. strain AQ5-05 - Darham, Syazani; Syed Muhaimin, Sharifah Nabilah Nursyuhada; Subramanian, Kavilasni; Zulkharnain, Azham; Shaharuddin, Noor Azmi; Abdul Khalil, Khalilah; Ahmad, Siti Aqlima (MDPI, 2021)
The versatility of a rare metal, molybdenum (Mo) in many industrial applications is one of the reasons why Mo is currently one of the growing environmental pollutants worldwide. Traces of inorganic contaminants, including Mo, have been discovered in Antarctica and are compromising the ecosystem. Bioremediation utilising bacteria to transform pollutants into a less toxic form is one of the approaches for solving Mo pollution. Mo reduction is a process of transforming sodium molybdate with an oxidation state of 6+ to Mo-blue, an inert version of the compound. Although there are a few Mo-reducing microbes that have been identified worldwide, only two studies were reported on the microbial reduction of Mo in Antarctica. Therefore, this study was done to assess the ability of Antarctic bacterium, Arthrobacter sp. strain AQ5-05, in reducing Mo. Optimisation of Mo reduction in Mo-supplemented media was carried out using one-factor-at-a-time (OFAT) and response surface methodology (RSM) approaches. Through OFAT, Mo was reduced optimally with substrate concentration of sucrose, ammonium sulphate, and molybdate at 1 g/L, 0.2 g/L, and 10 mM, respectively. The pH and salinity of the media were the best at 7.0 and 0.5 g/L, respectively, while the optimal temperature was at 10 °C. Further optimisation using RSM showed greater Mo-blue production in comparison to OFAT. The strain was able to stand high concentration of Mo and low temperature conditions, thus showing its potential in reducing Mo in Antarctica by employing conditions optimised by RSM.